2019
DOI: 10.14710/jitaa.44.2.220-227
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the sosial economic benefits of Jabres cattle keeping in Bantarkawung Sub-district, Brebes, Central Java, Indonesia

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi kebermanfaatan sosial ekonomi sapi Jabres sebagai ternak lokal potensial pada dua zona ekologi di Kecamatan Bantarkawung, Brebes, yaitu zona dataran rendah dan dataran sedang. Pengambilan data dilakukan dengan metode Participatory Rural Appraisal (PRA), yaitu pendekatan yang melibatkan keluarga atau individu untuk menganalisis realita dari kondisi kehidupannya. Penelitian ini melibatkan 60 peternak dipilih secara purposive sampling berdasarkan 3 pertimbangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Farmers with longer experience of raising livestock, tend to be open for information to change their traditional rearing patterns and overcome their difficulties [9]. The number of livestock owned by farmer influence their attitudes and decision about their livestock [10].…”
Section: Resultsmentioning
confidence: 99%
“…Farmers with longer experience of raising livestock, tend to be open for information to change their traditional rearing patterns and overcome their difficulties [9]. The number of livestock owned by farmer influence their attitudes and decision about their livestock [10].…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of formal credit scheme, sharing is the only source of the farmers to keep animals. The sharing arrangement helps farmers who would like to keep small ruminants but do not have enough capital (Budisatria et al, 2010), it was also easy and risk-avoiding for the farmers, since there was no debt payment burden (Haq et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The common belief is that the productivity of a farmer increases with age, reaches some mid-age peak, and then decreases with further age (Budisatria et al, 2019). Cattle farming experience was one of the important factors in improving cattle farming management to increase livestock production (Budisatria and Udo, 2013;Haq et al, 2019). The experience of the farmers was not significantly different.…”
Section: Farmers Profilementioning
confidence: 99%
“…They need to be continuously empowered in terms of input technologies, financial support, information, and markets. Haq et al (2019) suggested that the farmers with higher education levels would more quickly implement innovation. On the contrary, those with low education levels tended to avert innovation.…”
Section: Farmers Profilementioning
confidence: 99%